Advanced operation and control in graphical user interface of a membrane-integrated hybrid biochemical process for acetic acid production. Issue 1 (1st January 2021) - Nayak, Jayato; Pal, Parimal; Chakrabortty, Sankha; Dey, Pinaki; Kumar, Ramesh; Banerjee, Shirsendu; Soosai Antony, Jenish
ABSTRACT: Commercialisation of new generation biochemical processes demands additional tools for effective design, operation and control because such biochemical processes are quite sensitive to a number of operating variables that need close monitoring. This work presents the development of a need-based, object-oriented and menu-driven simulation tool with graphical user interface (GUI) for a three-stage membrane-integrated process meant for transforming waste cheese whey into high purity acetic acid. The user-friendly Visual Basic Plant Performance Analysis (VIBAPPA) simulation tool captures microbial fermentation kinetics in a continuous stirred tank bioreactor, microbial cell separation by microfiltration, product purification by nanofiltration and product concentration by forward osmosis. High accuracy in software simulation is well reflected in the overall correlation coefficient ( R 2 > 0.98) and the Willmott d -index ( d > 0.97). The GUI of software tool allows quick optimisation of the process parameters and continuous monitoring and control of the biochemical process plant with ease and confidence.